The Impact of Participation in Victim-Offender Mediation Sessions on Recidivism of Serious Offenders - Stewart, Lynn (International journal of offender therapy and comparative criminology, 2018)
The federal correctional agency in Canada offers victim-offender mediation services to address serious crime. The current study used survival analysis to compare revocation rates of 122 offenders who participated in facilitated face-to-face meetings to a matched sample of 122 of non-participants. Results indicated that there was no significant difference between revocation rates when offenders participated while incarcerated, although the trend was that participants did better. When the meetings were held in the community post-release, however, participants were significantly more likely to spend a longer period of time under supervision in the community without returning to custody and were less likely to be revoked than their matched counterparts. The findings support participation in restorative justice sessions while under community supervision for higher risk offenders with histories of serious and violent crimes. The authors discuss how factors not controlled in the matching procedure may have contributed to this effect.